Factors affecting Muslim employees' motivation in Islamic fund management company: a case study of Tabung Haji head quarter / Nor Erna Nabila Mohd Raffi - Mohd Raffi, Nor Erna Nabila (2014)
The purpose of this research was to identify the factor affecting Muslim employees' motivation in Islamic Fund Management Company. Besides that, the main factor that influenced the Muslim employees' motivation was also being studied between reward and recognition, administrative policies, employee's knowledge sharing, and Islamic values factor. Significant difference between the Muslim employees' motivation was also identified. Respondents in this research comprised of 100 employees in Tabung Haji Head Quarter. The questionnaire used to measure the level of motivation and the possible factors that influenced the respondents' motivation was designed based on the previous research. The Cronbach Alpha obtained from the pretest was 0.6330 and about 100 set of questionnaire forms were distributed to the Tabung Haji employees and the response rate was 100%. The answers were analyzes by several statistical test methods using Statistical Package for Social Science (SPSS) version 17.0. The overall mean scores Muslim employees' motivation resulted from descriptive statistics were positive and moderate with the Muslim employees' motivation. Based on Multiple Regression analysis, it was identified that administrative policies factor is the main factor that influenced the Muslim employees' motivation. The findings analyzed by ANOVA table also showed that this research have a fit of model as the result of the overall research show that it is below the level of significant of 0.05 which the result is 0.00. The implication and limitation of this research also were discussed. Suggestion and recommendation for the management of Tabung Haji, future researchers, and government were also given.